Small and Large Extracellular Vesicles From Human Preovulatory Follicular Fluid Display Distinct ncRNA Cargo Profiles and Differential Effects on KGN Granulosa Cells - Inge Varik; Katariina Johanna Saretok; Kristine Rosenberg; Ileana Quintero; Maija Puhka; Nataliia Volkova; Aleksander Trošin; Paolo Guazzi; Agne Velthut‐Meikas (Journal of Extracellular Vesicles)
ABSTRACT Follicular fluid extracellular vesicles (FF EVs) facilitate communication between oocytes and somatic cells within the ovarian follicle, playing a pivotal role in follicular development. This study highlights the molecular and functional distinctions between small (SEV) and large (LEV) FF EV subpopulations, revealing their specialised regulatory roles in granulosa cell (GC) biology and their consequential impact on ovarian function. Single‐EV profiling uncovered distinct tetraspanin distributions, with LEVs containing a lower proportion of CD9/CD63/CD81‐positive particles compared to SEVs. Fluorescent labelling confirmed uptake of both SEVs and LEVs by GCs, supporting their capacity to impact cellular behaviour. Functionally, LEVs increased testosterone production by GCs, whilst SEVs had no effect on steroid hormone secretion, suggesting a specific role for LEVs in androgen biosynthesis. Transcriptomic analysis revealed extensive SEV‐induced changes in GC gene expression, affecting pathways involved in transcription, TGF‐β signalling, extracellular matrix (ECM) remodelling and cell cycle regulation. In contrast, LEVs elicited minimal transcriptional changes, primarily modulating genes associated with immune regulation and oxidative stress defence. Small RNA sequencing further revealed distinct non‐coding RNA (ncRNA) profiles, with SEVs enriched in miRNAs targeting pathways critical for GC differentiation, whilst LEVs carried higher levels of piRNAs implicated in maintaining genomic stability. These findings advance our understanding of FF EV‐mediated intercellular communication and underscore the importance of investigating EV subpopulations independently.